Uma introdução à invariância conforme na Teoria das Cordas - Morales, Dumar Andres Ospina (2018)
In this work we study the formalism of Conformal Field Theory (CFT) and apply it to the theory of strings and superstrings. We also use the BRST quantization technique to obtain the string spectrum together with the celebrated critical dimension for the bosonic string, i.e. the d=26. By performing a supersymmetric extension of the Polyakov action of the bosonic string we construct a superstring, which now includes fermionic degrees of freedom as well. The gauged fixed action of the latter theory leads to the critical dimension d=10 after imposing the condition of the vanishing of the conformal anomaly at the quantum level.